2017
DOI: 10.1007/s12032-017-1044-9
|View full text |Cite
|
Sign up to set email alerts
|

Kefir: a powerful probiotics with anticancer properties

Abstract: Probiotics and fermented milk products have attracted the attention of scientists from various fields, such as health care, industry and pharmacy. In recent years, reports have shown that dietary probiotics such as kefir have a great potential for cancer prevention and treatment. Kefir is fermented milk with Caucasian and Tibet origin, made from the incubation of kefir grains with raw milk or water. Kefir grains are a mixture of yeast and bacteria, living in a symbiotic association. Antibacterial, antifungal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(90 citation statements)
references
References 55 publications
1
70
0
19
Order By: Relevance
“…; Sharifi et al . ). Health benefits comprise antimicrobial activity, tumour suppression; wound healing properties, immunomodulation, anti‐inflammatory, antiobesity, cholesterol lowering and antioxidant effects, improvement in lactose tolerance, alleviation of fatty liver and enhancement of intestinal bacterial flora.…”
Section: Health Promoting Properties Of Kefir Micro‐organismsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Sharifi et al . ). Health benefits comprise antimicrobial activity, tumour suppression; wound healing properties, immunomodulation, anti‐inflammatory, antiobesity, cholesterol lowering and antioxidant effects, improvement in lactose tolerance, alleviation of fatty liver and enhancement of intestinal bacterial flora.…”
Section: Health Promoting Properties Of Kefir Micro‐organismsmentioning
confidence: 97%
“…The functional and probiotic properties of kefir have been studied by numerous authors and the most relevant findings have been summarized properly (John and Deeseenthum 2015;Prado et al 2015;Bourrie et al 2016;Sharifi et al 2017). Health benefits comprise antimicrobial activity, tumour suppression; wound healing properties, immunomodulation, anti-inflammatory, antiobesity, cholesterol lowering and antioxidant effects, improvement in lactose tolerance, alleviation of fatty liver and enhancement of intestinal bacterial flora.…”
Section: Health Promoting Properties Of Kefir Micro-organismsmentioning
confidence: 99%
“…Kefir grains contain a natural microbial consortium composed of a diverse and stable community of bacterial and yeast species [15,16] embedded in an exopolysaccharide matrix called kefiran [17]. Several studies have demonstrated that the microbes present in kefir are probiotic have beneficial health properties, including antibiosis [18], hypocholesterolaemic [19], antihypertensive [20], and anti-inflammatory [21] effects, as well as antioxidant [22], and anti-carcinogenic activity [23].…”
Section: Introductionmentioning
confidence: 99%
“…The dairy industry provides the most popular probiotic-containing beverages due to the effective transport of live probiotics [89][90][91][92], which can be associated with various health-promoting effects [93][94][95][96][97][98][99][100][101][102][103][104]. In a study by Cordeiro et al [105] a mouse model of infection control caused by Salmonella typhimurium, showed that conventional fermented dairy beverages had a protective effect against pathogenic bacteria.…”
Section: Non-dairy In Vitro Blueberry Beverages Controlled Retinal Pimentioning
confidence: 99%